Parisinus Graecus 2957 e Vaticanus Urbinas Graecus 118: riflessioni intorno al rapporto stemmatico di due testimoni della tradizione lucianea - Brignone, Carlotta (Lexis, 2025)
The article focuses on the stemmatic relationship between two recentiores codes of Lucian’s manuscript tradition: the Parisinus gr. 2957 (siglum N) and the supplement of the Vaticanus Urbinas gr. 118 (siglum i). The positions taken by contemporary and last-century scholars, in fact, show some ambiguities regarding the issue. Through the integral collation of four works (Dipsades, Herodotus sive Aetion, Zeuxis sive Antiochus e Pro lapsu inter salutandum), an attempt is made to shed light. The conclusion we have come to is that i is not directly descended from N. The demonstration is also supported by an additional textual datum from the spurious work Asinus. Both manuscripts, in fact, bear a censored version of this text, but the censorship does not occur in exactly the same way. Finally, an attempt is made to propose a stemma codicum that can synthesize all the collected textual data, in which N-i descends from a common lost witness, named β5.